Answer From Entities Of The Public Finance Sector To The Idea Of New Public Governance – The Bsc In The Public Sector - Anna Stronczek; Elżbieta Marcinkowska (European Scientific Journal, ESJ, 2016)
The idea of new public governance puts emphasis on the proper determination of objectives and the monitoring of results, the effective management of finances, the determination of service standards, the use of benchmarking or human resources management. Such approach requires the implementation of appropriate tools supporting management processes. Therefore, it is very important to extend the accounting system of the entities from the public sector with methods and tools of management accounting. This article focuses on finding the answer to the question which tools of management accounting may be helpful and may support managing in entities from the public sector. First, we made a short review of previous research on the application of management accounting instruments in entities from the public sector. Next, we examined which tools and methods of management accounting intend to support the examined entities when they implement integrated IT systems and thus we learned which tools they use. Then, we paid special attention to the use of BSC in a public entity, namely a hospital.